2009
DOI: 10.1139/o09-010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alteration of translation error rate on enzyme microheterogeneity as assessed by variation in single molecule electrophoretic mobility and catalytic activity

Abstract: The role of translation error for Escherichia coli individual beta-galactosidase molecule catalytic and electrophoretic heterogeneity was investigated using CE-LIF. An E. coli rpsL mutant with a hyperaccurate translation phenotype produced enzyme molecules that exhibited significantly less catalytic heterogeneity but no reduction of electrophoretic heterogeneity. Enzyme expressed with streptomycin-induced translation error had increased thermolability, lower activity, and no significant change to catalytic or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The Winzor model [2] used suggested that the variance in mobility of the unmodified enzyme could be attributed to relatively small difference in size and effective charge. This is consistent with other studies [13][14][15]. The model gave plausible results for the prediction of changes in size, shape, and charge required to accompany the changes in observed mobilities of -galactosidase caused by labelling.…”
Section: Factors Affecting Electrophoretic Mobilitysupporting
confidence: 91%
See 1 more Smart Citation
“…The Winzor model [2] used suggested that the variance in mobility of the unmodified enzyme could be attributed to relatively small difference in size and effective charge. This is consistent with other studies [13][14][15]. The model gave plausible results for the prediction of changes in size, shape, and charge required to accompany the changes in observed mobilities of -galactosidase caused by labelling.…”
Section: Factors Affecting Electrophoretic Mobilitysupporting
confidence: 91%
“…Previous studies have suggested that the observed heterogeneity in electrophoretic mobility of individual enzyme molecules may result from relatively small differences in shape, size, and charge [13][14][15]. In order to assess this, -galactosidase was subjected to relatively small changes in its size, shape and charge through chemical modification.…”
Section: Resultsmentioning
confidence: 99%
“…An average 8% change in the widths of the box-shaped peaks corresponds to a calculated change in electrophoretic mobility of 1 x 10 -6 cm 2 V -1 s -1 . β-Glactosidase has a Stokes radius of 6.9 nm, an average buffer radius of 0.25 nm, an axial ratio of 1.31 and a net charge of -62.9 at pH 7.3 (Nichols et al 2009). If a conformational change resulted in a change in Stokes radius of less than 0.1 nm, this is sufficient to result in a change in mobility of 1 x 10 -6 cm 2 V -1 s -1 .…”
Section: R a F Tmentioning
confidence: 99%
“…β-Galactosidase has been found to be electrophoretically heterogeneous. With a Stokes radius of 6.9 nm, an average buffer radius of 0.25 nm, an axial ratio of 1.31 and a net charge of -62.9 at pH 7.3, a difference in conformation resulting in a change in radius of 0.3 nm is sufficient to account for nearly the entire range of the static electrophoretic mobility heterogeneity observed (Jacobson et al 1994;Johansson et al 2001;Nichols et al 2009).…”
mentioning
confidence: 99%
“…This observed heterogeneity is not limited to catalytic rate. Activation energy of catalysis (Craig et al 1996;Craig and Nichols 2008), K m (Craig et al 2010), V max (Craig et al 1996), electrophoretic mobility Craig and Nichols 2009), and dependence upon metal ions to maintain stability (Craig, Hall, and Goltz 2000) have also been found to vary amongst individual enzyme molecules. In addition, catalytic rate has been found to vary for a given enzyme molecule over time (Lu, Sun, and Xie 1998;Edman et al 1999;English et al 2006;Craig and Nichols 2008).…”
Section: Introductionmentioning
confidence: 99%